نظرية الشبكة في علم النفس المرضي: نظرة عامة - بن عزوزي, ابراهيم; قرشي, عائشة (جامعة الوادي - University of Eloued, 2019)
تعتبر نظرية الشبكة من أهم النماذج النظرية التي أنتجها العلم واستفاد منها علم النفس المرضي، بحيث ينظر هذا النموذج إلى الاضطراب النفسي على أنه مجموعة من الأعراض المترابطة فيما بينها بطريقة تسلسلية، بمعنى أن كل عرض هو في حد ذاته مسؤول عن ظهور العرض الآخر في سياق تفاعلي متبادل مع الخضوع لمبادئ خاصة ومحددة. ترتبط هذه الأعراض المحددة على شكل نقاط ضمن نموذج تحليل الشبكة بمجموعة من الحدود أو الحواف. The theory of the network is one of the most important theoretical models produced by science and benefited from the psychopathology, so that this model considers the psychological disorder as a set of symptoms interconnected in a sequential manner; that is, each symptom is itself responsible for the emergence of the other symptom in an interactive context Reciprocal and subject to specific and specific principles. These specific symptoms in nodes within the network analysis model are related to a set of edges.
The network theory in mental disorders: an overview
مقال
Keywords: نظرية الشبكة ، علم النفس المرضي ، النقاط ، الحدود; the network theory; psychological disorder; nodes; edges.